Empowering Clean Energy Justice: The Role of Logistic Performance, Digital Finance, and Political Stability - Al Humdan, Eias; Ben-Salha, Ousama; Soltani, Hassen; Ullah, Sana (International Journal of Energy Economics and Policy, 2025)
The SGD 7 underscores the significance of affordable and clean energy for all. As a result, clean energy justice has gained a lot of attention from academics and policymakers. Due to its significance for the world's sustainable future, finding the factors of clean energy justice has become crucial. This analysis aims to examine the influence of logistic performance, digital finance, and political stability on clean energy justice in 70 developing economies. Empirical analysis is performed via the use of two-stage least squares (2SLS), system generalized method of moments (SGMM), and smoothed instrumental variable quantile regression (SIVQR) techniques. The outcomes of the study highlight that logistics performance, digital finance, and political stability help foster clean energy justice. In addition, the GDP, globalization, ICT, and FDI contribute to clean energy justice, while natural resource rent proves detrimental to clean energy justice. In light of these findings, we suggest that policymakers formulate a policy for the fair and equitable distribution of clean energy with improved logistics performance, digitalization of the financial sector, and political stability as the main ingredients.